Educational Golf Game Tools as Program Edupreneur Early Childhood Education Teacher Education Study Program - Yasuli Bindulem; Putri Sari Ulfa Sembiring; Novi Cynthia Yusnita; Kharida Shaleha; Irma Herliza Rizky (Outline Publisher, 2024)
The mismatch between competence and job requirements is the cause of rampant unemployment. Moreover, an imbalance between demand and supply, as well as the quality of human resources is produced. The edupreneur program in the Early Childhood Teacher Education (PGPAUD) study program can equip graduates to be more competitive, especially looking for jobs with competency. This research aims to develop an educational game tool (APE) in the form of APE Golf as a form of entrepreneurship education program (edupreneur) in the PGPAUD study program. The method used is Borg and Gall research and development. The development of APE Golf was carried out in several stages, namely: the initial trial design stage given to material expert validators and media experts and the main field trial stage with 10 children. The results of this research indicate that APE golf is suitable to be used as an edupreneur program for students and prospective teachers in the PGPAUD Study Program. Testing APE golf with respondents can encourage student activity and develop fine and gross motor skills. APE golf can also be used as a learning medium in PAUD.